Pengenalan Digital Marketing Untuk Meningkatkan Penghasilan Peternak Ayam Kampung Di Koto Tangah Padang - Khairil Azmi; Jon Maizar; Nardiman Nardiman (Konsienti : Community Services Journal, 2023)
Starlight Green Farm is a free-range chicken farming business located on Jalan Air Cold Balai Gadang Koto Tangah Padang, where the service is being carried out to provide an introduction to digital marketing in these difficult times as a result of the Covid-19 Pandemic in February 2020 which is still impacting the Starlight business. Green Farm. There is still a lack of knowledge from business owners, which encourages this community service team to provide information about digital marketing regarding the use of information technology in marketing. With this activity, it is hoped that business owners will be motivated to use digital marketing in order to get opportunities and use it as a means of communication in increasing their business income. The methods used in this activity are lectures, questions and answers and simulations. Based on this, the solution provided to the Starlight Green Farm business is to provide material and an introduction to digital marketing to increase business income so that it is able to take advantage of marketing opportunities through online and offline media.